Value of cardiac magnetic resonance tissue tracking imaging for assessment of early cardiac function in rats with left ventricular remodeling - LI Haichen; LI Mei; HUANG Ruijue; WEN Xiaojuan; ZHANG Mingxing (陆军军医大学学报, 2023)
Objective To investigate the value of 7.0T cardiac magnetic resonance tissue tracking imaging (CMR-TT) in evaluation of cardiac function in rats with early left ventricular remodeling induced by isoproterenol (ISO). Methods Eighteen male healthy specific pathogen-free (SPF) SD rats were randomly divided into control (n=6) and model group (n=12).The rat model of early left ventricular remodeling was established by subcutaneous multipoint injection of 10 mg·kg-1·d-1 ISO solution for 10 d.After modeling, 7.0T CMR cine sequence scans were performed immediately, and the post-processing software CVI42.0 was used to analyze and compare the differences in each left ventricular (LV) function and myocardial strain parameters between the 2 groups of rats.Enzyme-linked immunosorbent assay (ELISA) was performed to detect cardiac troponin Ⅰ(cTn-Ⅰ) and N-terminal B-type natriuretic peptide (NT-pro BNP) levels in right atrial transvenous serum.Pearson correlation analysis was employed to analyze the correlation of left ventricular ejection fraction (LVEF), cTn-Ⅰ and NT-pro BNP levels with each overall myocardial strain parameter of LV. Results The results of imaging, serology and pathology displayed that that the model group showed obvious hypertrophy of the LV myocardium and different damage at each base of the myocardium, resulting in a significant decrease in conventional cardiac function and myocardial strain parameters of LV, which was the symbol of myocardial contractile dysfunction.Compared with the control group, heart mass (HM), heart mass index (HMI), left ventricular end-diastolic volume (LVEDV), left ventricular end-systolic volume (LVESV), left ventricular myocardial mass (LVM), left ventricular end-diastolic maximum wall thickness (LVEDTHmax), and left ventricular remodeling index (LVRI) were significantly greater in the rats of the model group (P < 0.05).LVEF, left ventricular global circumferential strain (LVGCS), left ventricular global radial strain (LVGRS), left ventricular global longitudinal strain (LVGLS), LVGRS-Mid-cavity, LVGRS-Apical, LVGCS-Mid-cavity, LVGCS-Apical, LVGLS-Basal, and LVGLS-Apical decreased in different degrees (P < 0.05).The changes in LVEF and cTn-Ⅰ and NT-pro BNP levels were all correlated with the changes in each overall LV myocardial strain parameter. Conclusion CMR-TT can be used to assess cardiac dysfunction in early left ventricular remodeling. x